Measuring and Exploring Children’s Health Literacy in The Netherlands: Translation and Adaptation of the HLS-Child-Q15 - Hahnraths, Marla T. H. (Int J Environ Res Public Health, 2021)
As health literacy (HL) is hypothesized to develop throughout life, enhancement during childhood will improve HL and health during life. There are few valid, age-appropriate tools to assess children’s HL. The German-language European Health Literacy Survey Questionnaire Adapted for Children (HLS-Child-Q15-DE) is a self-report questionnaire adapted from the adult European Health Literacy Survey Questionnaire. This study aims to translate the HLS-Child-Q15 to Dutch and explore the sample’s HL distribution. The HLS-Child-Q15-DE was translated following WHO guidelines and administered digitally to 209 Dutch schoolchildren (eight-to-eleven-year-olds). Its psychometric properties were assessed and the sample’s HL distribution was explored by demographic characteristics. The HLS-Child-Q15-NL had high internal consistency (α = 0.860) and moderate to strong item-total correlations (mean = 0.499). For 6 of the 15 items, >10% of participants answered “do not know”, indicating comprehension problems. Higher HL scores were observed for ten-to-eleven-year-olds (compared with eight-to-nine-year-olds; p = 0.021) and fourth-grade students (compared with third-grade; p = 0.019). This supports the idea that HL evolves throughout life and the importance of schools in this process. With the HLS-Child-Q15-NL, a Dutch measurement instrument of children’s HL is available, although it needs further tailoring to the target group. More research is needed to decrease comprehension problems and to investigate retest reliability and construct validity.